The “Black Straight-Line Sign” in the Putamen in Diffusion-Weighted Imaging: A Potential Diagnostic MRI Marker for Multiple System Atrophy - Zheng, Yiming; Wang, Xiwen; Zhao, Huajian; Jiang, Yanyan; Zhu, Ying; Chen, Jing; Sun, Wei; Wang, Zhaoxia; Sun, Yunchuang (Frontiers in Neurology, 2022)
Background and Purpose The diagnosis of multiple system atrophy (MSA) remains challenging in clinical practice. This study investigated the value of hypointense signals in the putamen ("black straight-line sign") in diffusion-weighted imaging (DWI) of brain MRI for distinguishing (MSA) from Parkinson’s disease (PD). Methods We retrospectively enrolled 30 MSA patients, 30 PD patients, and 30 healthy controls (HCs) who had undergone brain MRI between 2016 and 2020. Two readers independently assessed the signal intensity of the bilateral putamen on DWI. The putaminal hypointensity was scored using 4-point visual scales. Putaminal hypointensity and the presence of a “black straight-line sign” were statistically compared between MSA and PD or HC. Results The mean scores of putaminal hypointensity in DWI in the MSA group were significantly higher than in both the PD (U=315.5, P=0.034) and healthy control groups (U=304.0, P=0.022). Uni- or bilateral putaminal hypointensity in DWI with a score ≥2 was identified in 53.3% (16/30), 16.7% (5/30), and 13.3% (4/30) of MSA, PD, and healthy controls, respectively, with significant differences between MSA and PD (Χ2=8.864, P=0.003) or healthy controls (Χ2Χ2=10.800, P=0.001). Notably, the “black straight-line sign” of the putamen was observed in 16/30 (sensitivity 53.3%) patients with MSA, while it was absent in PD and HC (specificity 100%). There were no significant differences for the presence of “black straight-line sign” in the MSA-P and MSA-C groups (Χ2Χ2=0.433, P=0.510). Conclusion The "black straight-line sign" of the putamen in DWI of head MRIs has the potential to serve as a diagnostic marker for distinguishing MSA from PD.